Strength training effects on muscular regeneration after ACL reconstruction - Friedmann-Bette, Birgit; Profit, Francesca; Parstorfer, Mario; Weber, Marc-André; Streich, Nikolaus; Barié, Alexander (Medicine and science in sports and exercise, 2018)
Purpose Protracted quadriceps muscle atrophy is observed after anterior cruciate ligament reconstruction (ACL-R). The aim of this study was to assess if quadriceps strength training with eccentric overload (CON/ECC+) is more efficient to induce muscle regeneration after ACL-R than conventional concentric/eccentric (CON/ECC) strength training. - Methods Biopsies from the vastus lateralis muscle were obtained from 37 recreational athletes after 12 wk of regular rehabilitation after ACL-R and again after 12 wk with twice a week of either conventional CON/ECC (n = 16) or CON/ECC+ (n = 21) one-legged supervised leg-press training. Immunohistochemical analyses were used to determine satellite cell (SC) number (Pax7+); activated SC number (Pax7+/MyoD+); fibers expressing myosin heavy-chain (MHC) I and II, MHC neonatal, and fiber cross-sectional area. Magnetic resonance imaging was performed to measure quadriceps cross-sectional area and isokinetic testing for the measurement of quadriceps strength. - Results CON/ECC+ induced a significantly (P = 0.002) greater increase in quadriceps cross-sectional area than did CON/ECC. There also was a significant increase in the fiber cross-sectional areas of all fiber types and in quadriceps strength, but without significant difference between training groups. Only CON/ECC+ training led to a significant (P < 0.05) increase in percent type I fibers. After training, the number of MHC I+/MHCneo+ fibers was significantly (P < 0.05) greater in the CON/ECC+ than after in the CON/ECC group. The proportion of hybrid fibers tended to decrease in both groups; percent type II fibers, SC number, and activated SC number remained unchanged. - Conclusions CON/ECC+ leads to significantly greater muscle hypertrophy compared with CON/ECC, but without the hypothesized enhancing effect on SC activation. At the same time, CON/ECC+ induces a less favorable slower muscle phenotype for strong and fast movements.